Terapeutic hypothermia in neuroprotection has an impact on neuroplasticity in brain ischemia and trauma - F.V. Hladkykh; Т.І. Liadova; M.S. Matvieienko; D.V. Vasylyev (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. Thermoregulation maintains a stable body temperature, which is essential for normal physiological function. Therapeutic hypothermia is effectively used for neuroprotection in stroke, traumatic brain injury, increased intracranial pressure, and other conditions. Brain cooling reduces cellular damage, limits necrosis, and improves brain function. The optimal timing and duration of therapy depend on the specific condition. Hypothermia has significant potential when combined with other treatment methods, particularly pharmacological strategies, to enhance neuroprotection outcomes.